1995
DOI: 10.2165/00007256-199520030-00001
|View full text |Cite|
|
Sign up to set email alerts
|

Applied Physiology of Rugby League

Abstract: Rugby League is a game of physical contact that involves low-intensity, aerobic exercise, combined with periods of intermittent, intensive anaerobic exercise. Matches consist of two halves, each of 40 minutes, separated by a 10-minute recovery period, and are contested by 2 teams of 13 players (6 forwards and 7 backs). Whilst the amount of time spent by individual players on low-intensity exercise exceeds the duration of high-intensity exercise, the nature of the high-intensity efforts (involving sprinting, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 0 publications
1
46
0
2
Order By: Relevance
“…Some studies have suggested that rugby league players may benefit from higher subcutaneous fat levels as a means of protection from injury (Brewer, 1995;Meir, 1993). However, the majority of evidence suggests that carrying excess body fat has a negative effect on performance (eg.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that rugby league players may benefit from higher subcutaneous fat levels as a means of protection from injury (Brewer, 1995;Meir, 1993). However, the majority of evidence suggests that carrying excess body fat has a negative effect on performance (eg.…”
Section: Discussionmentioning
confidence: 99%
“…Professional teams and game popularity is most established in Great Britain, France, Australia and New Zealand (7,28) with the European Super League and Australasian National Rugby League the two major professional leagues in the world. Rugby league consists of frequent bouts of high intensity activity (e.g., sprinting, tackling, ball carrying) separated by bouts of low intensity activity (e.g., walking, jogging; 9, 13), requiring players to have highly developed aerobic and anaerobic capacities in order to compete at an elite level, due to the large distances covered and the high intensity activities undertaken during a game.…”
Section: Introductionmentioning
confidence: 99%
“…The game is most established in the UK, France, Australia and New Zealand (6,29), with the European Super League and Australasian National Rugby League the two major professional leagues. The game demands of rugby league are intermittent, with frequent bouts of highintensity activity (e.g., ball carrying, tackling) separated by low-intensity activity (e.g., jogging; 11,15).…”
Section: Introductionmentioning
confidence: 99%